Analysis of Risk Factors and Mortality of Patients with Carbapenem-Resistant Klebsiella pneumoniae Infection - Wu C; Zheng L; Yao J (Infection and Drug Resistance, 2022)
Cuiyun Wu,1 Lin Zheng,1 Jie Yao2 1Department of Clinical Laboratory, Shunde Hospital, Southern Medical University (The First People’s Hospital of Shunde), Foshan, Guangdong, People’s Republic of China; 2Department of Laboratory Medicine and Medical Research Center, Shunde Hospital, Southern Medical University (The First People’s Hospital of Shunde), Foshan, Guangdong, People’s Republic of ChinaCorrespondence: Jie Yao, Department of Laboratory Medicine and Medical Research Center, Shunde Hospital, Southern Medical University (The First People’s Hospital of Shunde), No. 1, Jiazi Road, Lunjiao, Shunde District, Foshan City, Guangdong Province, 528308, People’s Republic of China, Tel +86 757 22318169, Email jie.yao413@yahoo.comBackground: Carbapenem-resistant Klebsiella pneumoniae (CRKP) infection is associated with high mortality and has become a major public problem threatening patients. This study aimed to explore risk factors for death in patients with Klebsiella pneumoniae (KP) and identify risk factors for CRKP infection.Methods: The study retrospectively analyzed clinical characteristics and microbiological data from patients infected with KP from January 2019 to October 2021 to identify risk factors and mortality, using multivariate logistic regression analysis and Cox regression analysis.Results: A total of 214 KP inpatients were enrolled in our study. The in-hospital mortality rate was significantly higher in patients infected with CRKP (13/68, 19.12%) than carbapenem-susceptible KP (CSKP) (2/146, 1.37%) and the difference was statistically significant (P= 0.03). Multivariate Cox regression analysis showed CRKP isolation (HR 12.26, 95% CI 2.43– 61.68, P = 0.002), lower TP (HR 10.50, 95% CI 1.33– 82.76, P = 0.03), antibiotic days of therapy > 15 (HR 0.08, 95% CI 0.01– 0.56, P= 0.01) and length of stay (LOS) (HR 0.03, 95% CI 0.002– 0.61, P= 0.02) were independent risk factors for death from KP. Additionally, intensive care unit (ICU) stay (OR 21.69, 95% CI 4.50– 118.76, P< 0.001) and previous carbapenem exposure (OR 5.26, 95% CI 1.38– 21.19, P= 0.02) are independent risk factors for CRKP.Conclusion: Our findings showed that patients infected with CRKP have a higher in-hospital mortality rate. Identifying the independent risk factors for CRKP infection may contribute to the management of CRKP and reduce the mortality of KP patients.Keywords: carbapenem-resistant, Klebsiella pneumoniae, risk factors, mortality